2016
DOI: 10.1111/jocn.13261
|View full text |Cite
|
Sign up to set email alerts
|

‘Bringing respite in the burden of illness’ – dog handlers’ experience of visiting older persons with dementia together with a therapy dog

Abstract: Dog handlers use their skills and knowledge to promote a situation that reduces symptoms of illness and encourages healthier behaviour. The results of this study may be of interest to researchers, clinical practitioners, caregivers and dog handlers who care for persons with dementia using therapy dog teams on prescription as an alternative method to minimise behavioural and psychological symptoms of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Reductions in aggression and agitation were also reported (Peluso et al 2018;Charry-Sánchez, Pradilla, & Talero-Gutiérrez, 2018;Majić, Gutzmann, Heinz, Lang, and Rapp, 2013;Perkins, Bartlett, Travers, & Rand, 2008;Sellers, 2006). Social behaviour was reportedly improved for most participants (Peluso et al 2018;Thodberg et al 2016;Swall, Ebbeskog, Lundh Hagelin, & Fagerberg, 2016;Nordgren & Engström, 2012;Marx et al 2010;Perkins et al 2008;Kramer, Friedmann, & Bernstein, 2009;Filan & Llewellyn-Jones, 2006;Sellers, 2006). The presence of a skilled dog handler also impacted positively on many participants (Swall et al 2016;Perkins et al 2008).…”
Section: Animalsmentioning
confidence: 90%
See 1 more Smart Citation
“…Reductions in aggression and agitation were also reported (Peluso et al 2018;Charry-Sánchez, Pradilla, & Talero-Gutiérrez, 2018;Majić, Gutzmann, Heinz, Lang, and Rapp, 2013;Perkins, Bartlett, Travers, & Rand, 2008;Sellers, 2006). Social behaviour was reportedly improved for most participants (Peluso et al 2018;Thodberg et al 2016;Swall, Ebbeskog, Lundh Hagelin, & Fagerberg, 2016;Nordgren & Engström, 2012;Marx et al 2010;Perkins et al 2008;Kramer, Friedmann, & Bernstein, 2009;Filan & Llewellyn-Jones, 2006;Sellers, 2006). The presence of a skilled dog handler also impacted positively on many participants (Swall et al 2016;Perkins et al 2008).…”
Section: Animalsmentioning
confidence: 90%
“…Social behaviour was reportedly improved for most participants (Peluso et al 2018;Thodberg et al 2016;Swall, Ebbeskog, Lundh Hagelin, & Fagerberg, 2016;Nordgren & Engström, 2012;Marx et al 2010;Perkins et al 2008;Kramer, Friedmann, & Bernstein, 2009;Filan & Llewellyn-Jones, 2006;Sellers, 2006). The presence of a skilled dog handler also impacted positively on many participants (Swall et al 2016;Perkins et al 2008). Thodberg et al (2016) found that people with more advanced dementia interacted considerably more with the dog than with the human.…”
Section: Animalsmentioning
confidence: 99%
“…But, as seen in other studies, both animal and human visits resulted in the increase in positive social behaviors. [20][21][22][23] Respite programs are often underutilized. This underutilization is due in part to the family's belief that the program will result in negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Swall, Ebbeskog, Hageline, & Fagerberg studied nine dog-handlers trained in AAT who visited older persons with dementia. [23] The dog-handlers reported AAT brought respite from illness by tailoring visits for participants that were person-centered to increase quality of life and activity in those living with dementia. A meta-analysis of ten studies of animal-assisted interventions patients with cognitive impairment showed a statistically significant decrease in the behavioral and psychological symptoms of dementia such as disturbed behavior, mood, agitation and depression.…”
Section: Animal Assisted Therapymentioning
confidence: 99%
“…Previous research has shown that therapy dogs may function as a non-pharmacological alternative that works to decrease the challenging symptoms of dementia, including agitated behaviour, aggression and apathy (Nordgren and Engström, 2014;Martini de Oliveira et al, 2015;Swall et al, 2017;Scales, 2018). Therapy dogs have been shown to have a positive effect on the social behaviour of people with dementia and increase interaction with their environment, family and staff members (Bernabei et al, 2013;Swall et al, 2016) and decreased signs of depression (Perkins et al, 2008;Moretti et al, 2011;Mossello et al, 2011;Bernabei et al, 2013).…”
mentioning
confidence: 99%